1998
DOI: 10.1177/03635465980260060301
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Labral Injury in Contact Athletes

Abstract: Nine athletes (seven football offensive linemen, one defensive lineman, and one lacrosse player) were found at arthroscopy to have posterior labral detachment from the glenoid. In our series, this lesion is specific to contact athletes who engage their opponents with arms in front of the body. All patients had pain with bench pressing and while participating in their sport, diminishing their ability to play effectively. Conservative measures were ineffective in relieving their symptoms. Examination under anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 17 publications
4
112
0
2
Order By: Relevance
“…Primary mechanisms of injury may include: (1) an acute traumatic posteriorly directed shearing force along the glenoid face between the posterior labrum and glenoid articular surface, resulting in capsulolabral deta chment [13] ; (2) repetitive microtrauma to the posterior capsule, ultimately leading to capsular attenuation and labral tears [4] ; or (3) insidious onset of laxity of the posterior capsule and associated passive stabilizers [57] . Other causes of posterior instability often result from (1) excessive glenoid or humeral retroversion; (2) an engaging reverse HillSachs lesion; and (3) and glenoid hyperplasia [1,5] .…”
Section: Introductionmentioning
confidence: 99%
“…Primary mechanisms of injury may include: (1) an acute traumatic posteriorly directed shearing force along the glenoid face between the posterior labrum and glenoid articular surface, resulting in capsulolabral deta chment [13] ; (2) repetitive microtrauma to the posterior capsule, ultimately leading to capsular attenuation and labral tears [4] ; or (3) insidious onset of laxity of the posterior capsule and associated passive stabilizers [57] . Other causes of posterior instability often result from (1) excessive glenoid or humeral retroversion; (2) an engaging reverse HillSachs lesion; and (3) and glenoid hyperplasia [1,5] .…”
Section: Introductionmentioning
confidence: 99%
“…The role of posterior shoulder instability as a cause of disability in the athletic population has become increasingly recognized [5,12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Posterior instability in the athletic population more commonly arises from contact sports such as football and rugby and occurs from acute trauma [12,15] or repetitive microtrauma [20]. In the case of batter's shoulder, the major rotational forces about the shoulder are believed to be the cause of the instability [19].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in linemen. Mair et al 26 reported on nine athletes with posterior instability in which eight of nine were linemen and seven were offensive linemen. Often, these patients require surgery as Mair et al 26 also reported 75% required surgical stabilization.…”
Section: Direction Of Instabilitymentioning
confidence: 99%